Pembuatan Bioplastik Berbasis Komposit Pati Sagu-Carboxymethyl Cellulose (CMC) Dengan Plasticizer Sorbitol - Firdaus Septiawan; Said Zul Amraini; Bahruddin Bahruddin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The use of sago starch in production of bioplastic is an efforts to utilized natural resources in Riau Province. Carboxymethyl cellulose (CMC) and sorbitol can be added when the process for making bioplastic sago starch-based was carried out, to improve the quality of bioplastic. The aims of this research were to produced biodegradable plastic composite blends based on sago starch-CMC using sorbitol as plasticizer, to assess the effect of CMC and sorbitol as additional materials on mechanical properties, water uptake, and biodegradability of bioplastic, and also to determine mathematical relationship between the research parameters and the characteristics of bioplastic statistically using response surface method (RSM). This research were started by mixing sago starch, CMC (35, 40 and 45%w/w starch) and sorbitol (20, 25, 30 and 35% w/w total solid). Bioplastic obtained by this process were characterized by mechanical properties analysis, water uptake test, and biodegradability test. Based on the empirical equation obtained, the addition of CMC would increase the tensile strength, water uptake and biodegradability of bioplastic, while the addition of sorbitol would increase the percentage elongation of bioplastic. At optimum process condition, CMC 42,27% and sorbitol 24,25%, the best result with tensile strength 6,776 MPa, percentage elongation 18,134%, water uptake 69,418% and percentage biodegradation 55,459%.Keywords: bioplastic, carboxymethyl cellulose, response surface method, sago starch, sorbitol